1999
DOI: 10.1093/jnci/91.10.869
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Urokinase Receptor Levels in Patients With Colorectal Cancer: Relationship to Prognosis

Abstract: The preoperative plasma suPAR level independently predicted survival of patients with colorectal cancer. Further studies of plasma suPAR in patients with cancer are needed to evaluate the utility of plasma suPAR measurements and cut points in identifying high-risk patients among those with early stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
181
3
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(198 citation statements)
references
References 23 publications
8
181
3
6
Order By: Relevance
“…Increased serum levels of different uPAR forms have been associated with a poor prognosis in various cancers. 64,65 Reports concerning the ability of circulating uPAR to detect PCa are conflicting. McCabe et al 66 did not find any significant association between uPAR levels and the presence of PCa whereas Steuber et al 67 recently showed that uPAR fragments were significant predictors of PCa on biopsy specimens of patients with an elevated PSA.…”
Section: Urokinase Plasminogen Activation Systemmentioning
confidence: 99%
“…Increased serum levels of different uPAR forms have been associated with a poor prognosis in various cancers. 64,65 Reports concerning the ability of circulating uPAR to detect PCa are conflicting. McCabe et al 66 did not find any significant association between uPAR levels and the presence of PCa whereas Steuber et al 67 recently showed that uPAR fragments were significant predictors of PCa on biopsy specimens of patients with an elevated PSA.…”
Section: Urokinase Plasminogen Activation Systemmentioning
confidence: 99%
“…Under these conditions, uPAR is likely to be exposed to a proteolytic micro-environment in vivo where it may be solubilized by phospholipases or proteases, like plasmin, and even may enter the bloodstream, as has been implied by several authors (Ploug et al, 1992;Grøndahl-Hansen et al, 1995;Pappot et al, 1997;Stephens et al, 1997). Indeed, recent publications have shown that by measuring the soluble form of uPAR in peripheral blood important prognostic information in patients with colon (Stephens et al, 1999) or ovarian cancer (Sier et al, 1998) can be obtained. We are currently studying the prognostic role of soluble uPAR in blood samples obtained from patient undergoing surgery for primary breast cancer.…”
Section: Months Monthsmentioning
confidence: 99%
“…In human tumors, their high level is directly related to the decreased chances of disease-free survival (Reuning et al, 1998;Stephens et al, 1999;Dano et al, 2005). In some cancers, uPA and uPAR are expressed by cancer cells, whereas in others, they are expressed by stromal cells .…”
Section: Introductionmentioning
confidence: 99%